The Response of Node and Leaf Explant of Binahong (Anredera cordifolia L.) on MS Media with Variation of BAP Concentration - Triastuti Rahayu; Ucik Mardini (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The purpose of this study was to determine the response of nodal explants and leaves of plants binahong on MS medium with the addition of 2,4-D with BAP variation. Research was designed using two factors: factor 1: types of explants (E1 = node, E2 = leaf),  factor 2: the concentration of plant growth regulator BAP (B0 = 2,4-D 2 mg / L (without BAP); B1 = 2, 4-D 2 mg / L and BAP 1 mg / L; B2 = 2,4-D 2 mg / L and BAP 2 mg / L). Explants nodes and leaves of plants Binahong sterilized using Bayclin 45 "sterile distilled water and then rinsed 3 times further incubated in a culture room. Parameters include callus formation time (Days After Planting / HST), size, and color callus. Additional parameters: the presence or absence of roots and shoots. Observations made during the 35 days and the result that the treatment of E1 (explants nodes) more quickly induced to form callus and callus size larger than E2 (leaf explants). B0 treatment induced to form roots (E1 and E2), while B1 forming buds at E1. The conclusion is the response of nodal explants Binahong better for the formation of callus on MS medium with the addition of 2 ppm 2,4-D and variations in the concentration of BAP (0, 1, 2 ppm) compared explants of leaves and the most excellent in the treatment E1B1 (explants nodes on MS + 2 ppm 2,4-D and 1 ppm BAP).Keywords: Binahong, Callus, 2,4-D, BAP